Signaling in telecommunication networks - John G. van Bosse (Hoboken, N.J. : Wiley-Interscience, 2023)
The Second Edition of Signaling in Telecommunication Networks has been thoroughly updated, offering new chapters and sections that cover the most recent developments in signaling systems and procedures. This acclaimed book covers subscriber and network signaling in both fixed and mobile networks. Coverage begins with an introduction to circuit-switched telephone networks, including an examination of trunks, exchanges, access systems, transmission systems, and other basic components. Next, the authors introduce signaling concepts, beginning with older Channel Associated Signaling (CAS) systems and progressing to today's Common Channel Signaling (CCS) systems. The book then examines packet networks and their use in transmitting voice (VoIP), TCP/IP protocols, VoIP signaling protocols, and ATM protocols.